Pengaruh Konflik Kerja, Beban Kerja Serta Lingkungan Kerja Terhadap Semangat Kerja Karyawan - Singgih Hermawan (Forum Kerjasama Pendidikan Tinggi, 2023)
This study aims to determine the effect of work conflict, workload and work environment on employee morale. The type of research used in this research is quantitative research. Collecting research data using a questionnaire or questionnaire. The respondents of this research were 50 employees of PT. Gruti Lestari Pratama Sinunukan, Mandailing Natal. The data analysis technique uses multiple regression, so the data obtained is processed using SPSS 22. The results show that work conflict has a negative effect on morale, workload has a negative effect on morale, work environment has a positive effect on morale. The results of the F test show that the variables of work conflict, workload, work environment have a positive and significant effect on morale.